Empire of scholars : universities, networks and the British academic world, 1850-1939 - Pietsch, Tamson, 1978- (Studies in imperialism., 2015)
At the start of the twenty-first century we are acutely conscious that universities operate within an entangled world of international scholarly connection. Empire of scholars examines the networks that linked academics across the colonial world in the age of 'Victorian' globalization. Stretching across the globe, these networks helped map the boundaries of an expansive but exclusionary 'British academic world' that extended beyond the borders of the British Isles. Drawing on extensive archival research conducted in the United Kingdom, Canada, Australia, New Zealand and South Africa, this book remaps the intellectual geographies of Britain and its empire. In doing so, it provides a new context for writing the history of ideas and offers a critical analysis of the connections that helped fashion the global world of universities today.